Real Captivity in the Virtual World: A Review on Social Media Addiction - Mutlu, Sahabettin (Mus Alparslan Üniversitesi, 2025)
Increasing developments in audio-visual technology have led to communication and interaction between people being carried out mostly through social media. However, the intensive use of social media tools during the day has led to the emergence of different problems. The most common of these problems is social media addiction. Although this addiction is not yet included in diagnostic guidelines as a psychiatric diagnosis, it is discussed in the literature under the titles of social media addiction, problematic social media use and social media use disorder. A good understanding of this type of addiction is a priority requirement in the creation of prevention and intervention programs to reduce its negative effects. In this respect, it is necessary to present the theoretical framework of social media addiction in an accurate and comprehensive manner. For this reason, in the current study, the literature on social media addiction was reviewed and the results of national and international studies on the subject were compiled. As a result of the study, the conceptual framework of social media addiction, its causes, effects, prevalence, theories to explain social media addiction and ways of coping are presented. Within the framework of the results of this review, different recommendations have been put forward at the social and individual level. In addition, as a result of the review, suggestions are presented to researchers in line with the deficiencies observed in the research.

Görsel ve isitsel teknolojideki artan gelismeler insanlar arasindaki iletisim ve etkilesimin daha çok sosyal medya araciligiyla yürütülmesine yol açmistir. Ancak sosyal medya araçlarinin gün içerisinde yogun bir sekilde kullanilmasi da farkli problemlerin ortaya çikmasina neden olmustur. Bu problemlerden en yaygin olani ise sosyal medya bagimliligidir. Bu bagimlilik henüz psikiyatrik bir tani olarak tanilama kilavuzlarinda yer almasa da literatürde sosyal medya bagimliligi, sorunlu sosyal medya kullanimi ve sosyal medya kullanim bozuklugu basliklari altinda ele alinmaktadir. Bu bagimlilik türünün iyi anlasilmasi, olumsuz etkilerini azaltmaya yönelik önleme ve müdahale programlarinin olusturulmasinda öncelikli bir gerekliliktir. Bu açidan sosyal medya bagimliligina iliskin kuramsal çerçevenin dogru ve kapsamli bir sekilde ortaya konulmasi gerekmektedir. Bu gerekçeyle mevcut çalismada sosyal medya bagimliligina iliskin literatür taramasi yapilarak konuya iliskin ulusal ve uluslararasi çalismalarin sonuçlari derlenmistir. Çalisma sonucunda sosyal medya bagimliliginin kavramsal çerçevesi, nedenleri, etkileri, yayginligi, sosyal medya bagimliligini açiklamaya yönelik teoriler ve bas etme yollarina iliskin derleme sonuçlari sunulmustur. Bu derleme sonuçlari çerçevesinde de toplumsal ve bireysel düzeyde farkli öneriler ortaya konulmustur. Ayrica derleme neticesinde arastirmalarda gözlemlenen eksiklikler dogrultusunda arastirmacilara da öneriler sunulmustur.
Sanal Dünyada Gerçek Tutsaklik: Sosyal Medya Bagimliligi Üzerine Bir Derleme
Keywords: Drug Addiction Consultancy; Madde Bagimliligi Danismanligi; Psychological Counseling and Guidance (Other); Rehberlik ve Psikolojik Danismanlik (Diger)